European traded gas hubs: German hubs about to merge - Patrick Heather (The Oxford Institute for Energy Studies, 2021)
This Paper gives the results of the Author's analysis of the European traded gas hubs in 2020, as well as discussing the trading prospects for the new merged German gas hub, the Trading Hub Europe which is due to be operational from October 2021; it also compares the global gas benchmarks, Henry Hub, TTF, NBP and JKM. The merger of the German NCG and GPL hubs into one national hub is the culmination of a process of rationalisation started in 2008 when there were still 19 gas balancing zones. The stated aim of the Federal law which has mandated the merger is to increase liquidity in the gas market, and the German TSOs have the ambition for the new hub to be an international hub linking the German with other European gas markets. Given the country's large physical consumption and total physical throughput, this should be a possibility but begs the questions of why the NCG and GPL have not developed more than they have and whether, if that is due to there being two hubs rather than one, simply merging them will now have the desired effect? Unfortunately, the statistical data and the French experience of hub mergers suggest that it will struggle to succeed. On the wider European level, the vision set out some 20 years ago of a fully liberalised traded gas market is now almost fulfilled, with just a few more changes needed to be made, especially in eastern and south eastern Europe. The results of the 5 Key Elements for 2020 show an overall increase in European traded volumes, although not all hubs benefited. The TTF has consolidated its position at the top of the rankings and has increased both its 'net' and 'gross' churn rates; it is a mature and very liquid hub. At a global level, Henry Hub is the most liquid traded benchmark gas hub. TTF (and NBP to a lesser extent) is an important benchmark in its own market area and is also a benchmark for its region. JKM is the leading price market in Asia. The final conclusion of this Paper is that the political will in Ukraine could see it become a SEE regional hub in the future; that the TTF is most likely to remain the European gas price benchmark as well as a global benchmark; and that the new German Trading Hub Europe is very unlikely to reflect its name.
Keywords: 330; European (traded) gas hubs; Gas benchmarks; Gas price benchmarks; German hubs merger; Global churn rates; Global gas benchmarks; Henry Hub; JKM; THE; Trading Hub Europe; TTF